Plasma iron and iron delivery to the tissues - Graham, Ross; Chua, A.; Trinder, D. (Humana Press, 2012)
Iron is a transition element which has two biologically important oxidation states, +2 and +3. It is an essential trace element and, as such, takes part in a large number of varied biological processes, many of which utilize the interconversion of ferrous and ferric iron. Ferrous iron is relatively soluble but is readily oxidized to the ferric form which is sparingly soluble at physiological pH and will precipitate if not solubilized. It is also possible for the electron released from the oxidation reaction to participate in the formation of reactive oxygen species which can cause oxidative damage if present in high enough concentrations. Consequently, many elegant processes have evolved which render iron both soluble and non-toxic, allowing organisms to accumulate iron in forms which are both safe and functional.This chapter will provide an overview of the normal processes of iron transport in mammals, including a summary of the transport molecules and their mechanisms of iron capture and release. We will also outline the mechanisms of iron acquisition by tissues and the regulation of these processes.